2290. Identification of Pathogens in Synovial Fluid Samples With an Automated Multiplexed Molecular Detection System. (26th November 2018) - Pons, Benedicte; Jay, Corinne; Martin, Thibault; Sothier, Isabelle; Savelli, Helene; Kensinger, Bart; Laurent, Frédéric; Abad, Lelia; Murphy, Caitlin; Craney, Arryn; Schmitt, Bryan; Waggoner, Amy; et al.
Abstract: Background: Bone and Joint Infections (BJI) have high morbidity and are difficult to treat infections. Culture-based diagnosis is limited in its ability to recover fastidious bacteria and because several organisms can be involved; culture times of up to two weeks may be necessary for certain bacteria. The sensitivity of culture is also negatively impacted by antibiotics received before surgery. Alternatively, molecular methods offer a promising improvement for the diagnosis of BJI. The goal of this study was to evaluate a development version of Biofire ® Bone and Joint Infection (BJI) Panel (bioMerieux SA, BioFire Diagnostics, LLC) using synovial fluid samples. Methods: 121 synovial fluid specimens were collected from patients with suspected bone and joint infection in a pilot evaluation. All specimens were collected and tested in culture by the sites using their standard of care practices; in parallel, a leftover volume of 200 µL was tested on the BJI panel. BJI panel results were then compared with culture and discordant results were investigated using a comparator assay (PCR/sequencing). Results: 49 synovial fluid specimens (40%) were positive by culture vs. 72 with the BJI panel (59%). Of the 97 positive detections by the BJI panel, 58 were concordant with culture; the 39 additional organism detections were in majority confirmed by PCR/sequencing. Lastly, two false negative results corresponding to the same sample are under investigation. Conclusion: The BJI Panel was able to identify most of the pathogens detected by culture. The majority of additional detections observed were confirmed by PCR/sequencing. While sites are currently enrolling more synovial fluids samples, these preliminary data suggest that a multiplexed molecular test may be more sensitive than culture to detect pathogens in synovial fluid specimens. The data presented in this abstract have not been reviewed by FDA or other regulatory agencies for In Vitro Diagnostic use. Disclosures: B. Pons, bioMerieux: Employee, Salary. C. Jay, bioMerieux: Employee, Salary. T. Martin, bioMerieux: Employee, Salary. I. Sothier, bioMerieux: Employee, Salary. H. Savelli, bioMerieux: Employee, Salary. B. Kensinger, bioFire a bioMerieux company: Employee, Salary. F. Laurent, BioFire (bioMerieux company): Investigator, Research support. L. Abad, BioFire (bioMerieux company): Investigator, Research support. C. Murphy, BioFire (bioMerieux company): Investigator, Research support. A. Craney, BioFire (bioMerieux company): Investigator, Research support. B. Schmitt, BioFire (bioMerieux company): Investigator, Research support. A. Waggoner, BioFire (bioMerieux company): Investigator, Research support. S. Butler-Wu, BioFire (bioMerieux): Investigator, Research support. C. Costales, BioFire (bioMerieux company): Investigator, Research support. J. Bien-Bard, BioFire (bioMerieux): Investigator, Research support. J. Mestas, BioFire (bioMerieux): Investigator, Research support. J. Esteban, BioFire (bioMerieux): Investigator, Research support. L. Salar-Vidal, BioFire (BioMerieux company)): Investigator, Research support. A. Harrington, BioFire (bioMerieux company): Investigator, Research support. S. Collier, BioFire (BioMerieux Company): Investigator, Research support. A. Leber, BioFire (bioMerieux company): Investigator, Research support. K. Everhart, BioFire (bioMerieux company): Investigator, Research support. J. M. Balada-Llasat, BioFire (bioMerieux company): Investigator, Research support. J. Horn, BioFire (bioMerieux company): Investigator, Research support. S. Magro, bioMerieux: Employee, Salary. K. Bourzac, BioFire a bioMerieux company: Employee, Salary.